Porcupine bezoar exhibit as anti-cancer activities on human breast adenocarcinoma cells (MCF-7) - Firus Khan, Al'aina Yuhainis; Jalal, Tara Kamal; Abdull Rasad, Mohammad Syaiful Bahari; Hashim, Ridzwan; Abdul Wahab, Ridhwan (USM, 2016)
Purpose: Currently there were many treatments available to treat cancer patients, for instance chemotherapy, radiation therapy, immune therapy, and many more. Unfortunately, advancement in cancer therapy has resulted in increasing numbers of survivors which left to deal with side effects of their treatments. Therefore, discovery of alternative treatment with minimal side effect is crucial. Thus, study on bezoar take place as there were no scientific studies about porcupine bezoar to this date in Malaysia. This lead to the premise that porcupine bezoar could have greater potential for the chemoprevention activities. Methods: MCF-7 cells were treated with bezoar for cell proliferation, cell cycle, apoptosis and qPCR analyses. Cell viability of treated and untreated MCF-7 was examined by Trypan Blue Exclusion method. The cellular morphology of MCF-7 cells was observed by phase contrast microscopy. Flow cytometry analyzed cell apoptosis with annexin V/ propidium iodide (PI) and cell cycle with PI. qPCR was run in detecting gene expression involved in the apoptosis and cell cycle arrest. Result(s): Based on the conducted study and experiments, it is evident that the bezoar treatment in human periodontal ligament cells didn’t show cytotoxicity effect. Upon treated with optimized concentration of bezoar for 24, 48 and 72 hours, it shows inhibition of proliferation by 45.5, 31.25 and 37.1% respectively, significantly apoptosis and cell cycle arrest occurs. Bezoar treatment also induced apoptotic-liked in morphological changes. Upon qPCR analysis, its indicated mcf7 undergo intrinsic pathway of apoptosis and arrest at G1/G0 as gene expression high in cdk2, cyclin D and p21. Conclusion(s): Porcupine bezoar can be alternative treatment for cancer with minimal side effects. Yet, furthermore insights need to be studied.